Characterization of molybdenum disulfide nanomaterial and its excellent sorption abilities for two heavy metals in aqueous media. Issue 6 (13th April 2019) - Dong, Lijia; Li, Qian; Liao, Qing; Sun, Chunyan; Li, Xue; Zhao, Qingzhou; Shen, Runpu; Zhao, Baoshan; Asiri, Abdullah M.; Marwani, Hadi M.; Wu, Xilin; Hu, Baowei
ABSTRACT: Here, molybdenum sulfide (MoS2 ) was characterized and its performance as an adsorbent for Co(II)/Ni(II) removal from water was estimated in batch experiments. The nanomaterial exhibits thin-layered structure and contains numerous hydroxyl groups. High pH enhanced Co(II)/Ni(II) sorption, while ionic strength had no effect. The chemical sorption between the binding sites of MoS2 and Co(II)/Ni(II) limited the rate. The Freundlich isotherm correlated better than Langmuir isotherm. The maximum sorption capacity for Co(II)/Ni(II) was 370.10/375.94 mg· g −1, obviously exceeding other adsorbents. Both adsorptions were endothermic and spontaneous processes. This study indicates the intrinsic value of MoS2 in removing heavy metals from water.